2003
DOI: 10.1590/s0100-69912003000600002
|View full text |Cite
|
Sign up to set email alerts
|

Influência da glutamina na mucosa do instestino de ratos submetidos à enterectomia extensa

Abstract: OBJETIVO: Avaliar a influência de uma dieta suplementada com glutamina sobre as alterações adaptativas no intestino delgado de ratos com enterectomia extensa. MÉTODO: Vinte ratos Wistar, divididos aleatoriamente em dois grupos de dez animais, foram enterectomizados e alimentados com dois tipos diferentes de dieta nos 14 dias de pós-operatório: grupo controle (GC)-dieta padrão; grupo glutamina (GG)-dietapadrão acrescida de 3,05% de glutamina. Avaliou-se evolução ponderal, peso da mucosa intestinal (PM), profund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…9 Glutamine supplementation has been used in clinical and experimental situations of trophic reduction and intestinal absorption damage, although its real efficiency has not yet been proved. [20][21][22] When associated with growth hormone, glutamine supplementation has been shown to have a gut-trophic effect and to enhance intestinal absorption, both experimentally 4,22 and in clinical studies. 17 However, other researchers have not found considerable improvement with the association of glutamine and growth hormone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Glutamine supplementation has been used in clinical and experimental situations of trophic reduction and intestinal absorption damage, although its real efficiency has not yet been proved. [20][21][22] When associated with growth hormone, glutamine supplementation has been shown to have a gut-trophic effect and to enhance intestinal absorption, both experimentally 4,22 and in clinical studies. 17 However, other researchers have not found considerable improvement with the association of glutamine and growth hormone.…”
Section: Resultsmentioning
confidence: 99%
“…All animals underwent an extensive small bowel resection, including the ileocecal valve, leaving a remnant jejunum of only 25 cm from the pylorus that was anastomosed lateral-laterally to the ascendant colon. The animals were weighed at the beginning and end of the experiment (20 th postoperative day). Then they were killed and the remnant intestine was removed.…”
mentioning
confidence: 99%
“…Experimental and clinical studies have demonstrated the possible benefits with the use of this association in the treatment of intestinal insufficiency, after extensive resection of the small bowel [13][14][15][16][17][18][19][20] . Iglesias and Zucoloto 27 had indicated that the adaptative intestinal reactions initiate in the first few days after enterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…There are evidences that glutamine (GL) is the principal fuel for enterocytes [11][12][13] . Curiously, some experimental works 14,15 using diets rich in GL have not achieved good results in experimental SBS. However, the combined use of GL and GH may induce important trophic effects on the intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%